Testing a new form to document 'Goals‐of‐Care' discussions regarding plans for end‐of‐life care for patients in an Australian emergency department. (16th April 2018) - Mills, Amber C; Levinson, Michele; Dunlop, William A; Cheong, Edward; Cowan, Timothy; Hanning, Jennifer; O'Callaghan, Erin; Walker, Katherine J
Abstract: Objective : There is limited literature to inform the content and format of Goals‐of‐Care forms, for use by doctors when they are undertaking these important conversations. Methods : This was a prospective, qualitative and quantitative study evaluating the utility of a new 'Goals‐of‐Care' form to doctors in a private, tertiary ED, used from December 2016 to February 2017 at Cabrini, Melbourne. A Goals‐of‐Care form was designed, incorporating medical aims of therapy and patient values and preferences. Doctors wishing to complete a Not‐for‐CPR form were also supplied with the trial Goals‐of‐Care form. Form use, content and patient progress were followed. Doctors completing a form were invited to interview. Results : Forms were used in 3% of attendances, 120 forms were taken for use and 108 were analysed. The median patient age was 91, 81% were Supportive and Palliative Care Indicators Tool (SPICT) positive and patients had a 48% 6‐month mortality. A total of 34 doctors completed the forms, 16 were interviewed (two ED trainees, 11 senior ED doctors and three others). Theme saturation was only achieved for the senior doctors interviewed. Having a Goals‐of‐Care form was valued by 88% of doctors. The frequency of section use was: Aims‐of‐Care 91%; Quality‐of‐Life 75% (the term was polarising); Functional Impairments 35%; and Outcomes of Value 29%. Opinions regarding the ideal content and format varied. Some doctors liked free‐text space and others tick‐boxes. The median duration of the conversation and documentation was 10 min (interquartile range 6–20 min). Conclusions : Having a Goals‐of‐Care form in emergency medicine is supported; the ideal contents of the form was not determined.